Synthesis and characterisation of bismuth phosphate-based sillenites - Lee, S. L.; Lee, C. K.; Sinclair, D. C. (Elsevier Science B.V., Amsterdam., 2005)
Compounds in the Bi2O3–P2O5 binary system with Bi/P ratios of 13:1 to 16:1 crystallize with the sillenite structure (space group I23) and form a solid solution with the cubic lattice parameter increasing from 10.1660(4) to 10.1765(1) 2 with increasing Bi/P ratio. Differential thermal analysis (DTA) shows these compounds to exhibit complex thermal behaviour on thermal cycling with the presence of at least two endotherms above 800 8C on heating and at least three exotherms on cooling (all >630 oC). Impedance spectroscopy measurements as a function of temperature and oxygen partial pressure on the 14:1 composition show it to be a mixed n-type electronic and oxide-ion conductor at temperatures below 750 8C. Substitution of P by V and As in Bi/P=14:1 results in the formation of partial (30 at.%) and complete solid solutions, respectively. An enhancement in conductivity is observed in these solid solutions with V-doped materials exhibiting the highest conductivity with r~27 mS cm-1 at 800 oC for Bi14P0.7V0.3Od. Substitution of P by elements such as Pb, Sr, Al, Ga, Fe, Si, Ge and Ti leads to the formation of limited solid solutions. Most of these materials have similar or slightly higher total conductivity compared to the parent compound.